FOOD QUALITY SCHEMES IN THE EUROPEAN UNION: A BIBLIOMETRIC ANALYSIS - NICA IONUȚ; SBÎRCEA ROBERT ȘTEFAN*; MOCANU STELIANA; TUDORACHE CLAUDIU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
The food quality schemes implemented in 1992 by the European Union (EU) are present on every market nowadays, the consumers being oriented more than ever on the quality of products. The main three quality schemes developed by EU are: Protected Designations of Origin (PDO), Protected Geo-graphical Indications (PGI) and Traditional Specialties Guaranteed (TSG). However, a weak point was identified in the market of products bearing EU designations, namely the lack of knowledge of consumers for these products. Through a bibliometric analysis, the present research examines the articles on the topic of “food quality schemes AND European Union” in order to highlighting and identifying good practices and future directions of research that can be useful for other researchers regarding the food quality schemes to help with the increasing awareness and interest regarding these products. After the query the Web of Science (WoS) database, resulted a number of only 108 scientific documents containing the terms “food quality schemes AND European Union” in the title, abstract or keywords. After the bibliometric analysis, the results shows that the number of papers published with the topic “food quality schemes AND European Union” was fluctuating in the period 2015-2024, the highest number of these articles being framed into Food Science Technology WoS Category (23 articles), the highest number of articles published by one author from Italy (28 articles, 26% out of the total), the countries with the highest contribution on this topic being Italy, in connection with Greece, Portugal, Romania and Turkey. The most used keyword are quality and food, and the most recent keywords used in research are food safety, protected designation, label and geographical indication. The article with the highest number of citations is “PCR technology for screening and quantification of genetically modified organisms (GMOs)” (Holst-Jensen et al., 2003), with 304 citations and the most articles taken into consideration for the bibliometric analysis are in connection with SDG 03 - Good Health And Well Being (64%). One of the conclusions of this study is that a big part of the articles is written close to themes related to health, benefits and safety, aspects about that the consumers are also interested, this direction looks that can be a strategy od future campaigns of awareness among consumers regarding the EU certified products.